Application of Langmuir probe and optical emission spectroscopy for bromofluorocarbon plasma diagnostics. Issue 1 (April 2021) - Kuzmenko, V; Miakonkikh, A; Rudenko, K
Abstract: The Langmuir probe and optical emission spectroscopy were applied for diagnostics of C2 F4 Br2 low-pressure inductively coupled plasma. Electron temperature, plasma potential and concentrations of electrons, and positive ions, as well as fluorine and bromine radicals, were determined. An explanation of the results of experiments on the etching of low-k dielectrics in the studied plasma was proposed.